The reality of specialized educational supervision of secondary education in Iraq and the requirements for its development (Journal of the College of Basic Education, 2022)
The recent and rapid developments in our contemporary world and with the beginning of the third millennium imposed major changes on the various organizations and societies in terms of organization, culture and restructuring, which was directly reflected on these organizations and their impact on the individual and society as a whole.